167. A Phase 1b, Randomized, Double-blind, Placebo-controlled, Multiple-ascending Dose Study to Investigate the Safety, Tolerability, and Pharmacokinetics of DSTA4637S in Patients with staphylococcus Aureus Bacteremia Receiving Standard-of-care Antibiotics. (31st December 2020) - Lim, Jeremy; Lewin-Koh, Nicholas; Chu, Tom; Rymut, Sharon M; Berhanu, Aklile; Carrasco-Triguero, Montserrat; Rosenberger, Carrie C; Hazenbos, Wouter L; Miller, Loren G; Fowler, Vance G; Miro, Jose M; Couch, Jessica A; et al.
Abstract: Background: New treatment approaches for complicated Staphylococcus aureus bacteremia (SAB) are needed. DSTA4637S is a THIOMAB TM antibody-antibiotic conjugate consisting of an engineered human IgG1 monoclonal antibody that binds to wall teichoic acid at the surface of S. aureus, a protease-cleavable linker, and a novel rifamycin class antibiotic, dmDNA31. This Phase 1b study assessed the safety, tolerability, and pharmacokinetics of DSTA4637S in patients with complicated SAB. Methods: Multicenter, double-blind, placebo controlled, multiple-ascending dose clinical trial. Patients 18–79 years old with complicated SAB requiring at least 4 weeks of IV anti-staphylococcal standard-of-care (SOC) antibiotics were randomized to receive 4–6 doses of 15, 45, and 100 mg/kg IV DSTA4637S or placebo (6 active:2 placebo) every 7 days in combination with SOC antibiotics. Patients needed ≥ 1 blood culture positive for S. aureus collected within 120 hours prior to randomization. Patients were followed for 120 days after the end of treatment. Results: Twenty-five patients with complicated SAB (bone & joint, n=14; endocarditis, n=5; other endovascular, n=5; pneumonia, n=1) were randomized and received 1–6 doses of study drug (19 active:6 placebo). Nine patients (36%) had MRSA. Ten patients completed ≥4 doses of DSTA4637S. The most common treatment-related adverse events were infusion-related reactions (IRRs) (5/19), and abnormal serum color (5/19)/skin discoloration (3/19 (due to dmDNA31). IRRs were not dose-dependent and were reversible with supportive care. Ten of 19 patients (40%) discontinued study drug (9 DSTA4637S, 1 placebo); 4/19 (21%) due to IRR. DSTA4637S recipients showed no dose-related changes in laboratory values or vital signs vs. placebo. Observed exposures (Cmax and AUC) were lower in patients immediately after dosing compared to a prior study in healthy volunteers; minimal accumulation occurred. No obvious trends in exploratory bacterial and inflammatory biomarkers were observed between treatment groups. Conclusion: DSTA4637S in patients with complicated SAB demonstrated increased IRRs and decreased exposure compared to healthy volunteers, highlighting the importance of Phase I studies of novel treatments in infected SAB patients and not simply healthy controls. Disclosures: Jeremy Lim, PharmD, Roche (Employee, Shareholder) Nicholas Lewin-Koh, PhD, Genentech (Employee) Tom Chu, MD, PhD, Genentech (Employee) Sharon M. Rymut, PhD, Genentech (Employee, Shareholder) Aklile Berhanu, PhD, Genentech, Inc. (Employee, Equity interest (Stock/Stock Options)) Montserrat Carrasco-Triguero, PhD, Genentech (Employee) Carrie C. Rosenberger, PhD, Genentech (Employee, Shareholder) Wouter L. Hazenbos, PhD, Genentech (Employee) Loren G. Miller, MD, MPH, genentech (Grant/Research Support) Vance G. Fowler, Jr., MD, MHS, Achaogen (Consultant)Actavis (Grant/Research Support)Advanced Liquid Logics (Grant/Research Support)Affinergy (Consultant, Research Grant or Support)Affinium (Consultant)Allergan (Grant/Research Support)Ampliphi Biosciences (Consultant)Basilea (Consultant, Research Grant or Support)Bayer (Consultant)C3J (Consultant)Cerexa (Consultant, Research Grant or Support)Contrafect (Consultant, Research Grant or Support)Cubist (Grant/Research Support)Debiopharm (Consultant)Destiny (Consultant)Durata (Consultant)Forest (Grant/Research Support)Genentech (Consultant, Research Grant or Support)Integrated Biotherapeutics (Consultant)Janssen (Consultant, Research Grant or Support)Karius (Grant/Research Support)Locus (Grant/Research Support)Medical Biosurfaces (Grant/Research Support)Medicines Co. (Consultant)Medimmune (Consultant, Research Grant or Support)Merck (Consultant, Research Grant or Support)NIH (Grant/Research Support)Novadigm (Consultant)Novartis (Consultant, Research Grant or Support)Pfizer (Grant/Research Support)Regeneron (Consultant, Research Grant or Support)Tetraphase (Consultant)Theravance (Consultant, Research Grant or Support)Trius (Consultant)xBiotech (Consultant) Jose M Miro, MD PhD, GENENTECH (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member) Jessica A. Couch, PhD, Genentech (Employee, Shareholder) Melicent C. Peck, MD, PhD, Genentech (Employee)